Intellectual Initiatives of the Iranian and Kazakh Intelligentsia in the 20-30s of the XX Century - Rakhimova, Kalamkas; Batyrkhan, Bolatbek (Journal of Posthumanism, 2025)
The article examines the role of the Iranian and Kazakh intelligentsia in the process of modernization. We are talking about the struggle for the independence of the country at the beginning of the twentieth century and the modernization of the consciousness of traditional society. The historical experience of the Kazakh and Iranian intelligentsia was studied, as well as the goals and objectives set by the intellectuals of the two countries on this path, the path of their struggle. The ideas of intellectuals of both countries regarding nationalism and colonialism are analyzed, including their reaction to European imperialism and their efforts to promote national independence. In the twentieth century, a comparative analysis was conducted of how intellectuals reacted to the challenges of modernization and secularization, how their ideas and values changed over time, their ideas about nationalism and identity, including how language, culture and history played an important role in the formation of national identity. The author speaks about the gradual transition of the ideas of enlightenment of the intelligentsia of the nation to the idea of political reforms, that is, reforms at the state level, about the process of introducing this idea into the national idea. The reasons for the emergence of these ideas and the functions they perform were analyzed. The article presents a historical and comparative analysis of the intellectual activity of the Iranian and Kazakh intelligentsia of the early twentieth century. To this end, an attempt was made to conduct a study of the activities and ideological initiatives of the intelligentsia of the two countries using methods of historical comparison and comparison, historical description and analysis.